Sankhya the Indian Journal of Statistics Volume 16, Parts I and 2, December, 1955 - Planning Commission (Planning Commission, 1955)
The Draft Plan-frame of 17 March 1955 giving Recommendations for the Formulation of the Second Five Year Plan of India (to be referred to subsequently as the Plan-frame) together with extracts from the associated working paper of 21 March 1955 prepared jointly by the Economic Division of the Ministry of Finance, and the Economic Division of the Planning Commission in consultation with the Central Statistical Organization and the Indian Statistical Institute, and a memorandum giving "Basic Considerations Relating to the Plan-frame" prepared on 10 April 1955 by the Panel of Economists of the Planning Commission are being reproduced as appendices by the courtesy of the Planning Commission.
Statistical Publishing Society
Statistical Publishing Society